A Letter from a Tatar warrior to his wife - Abibullaeva E.E. (Золотоордынское обозрение)
Purpose of the study: to identify sources on everyday life during the Crimean Khanate. An attempt to reconstruct individual episodes of everyday life through the study and reference to materials of the epistolary genre. Research materials: The article analyzes and translates into Russian a letter from Suleiman Effendi to his wife, presumably written during the Polish-Turkish War (1632–1634). This letter was published in 1864 in the collection of V. Velyaminov-Zernov “Materials for the history of the Crimean Khanate”, but until today it remained completely unexplored. Results and scientific novelty: The topic of everyday life during the Crimean Khanate period remains unstudied and unconsidered. In view of this circumstance, the relevance of the problem raised in the study lies in identifying and considering sources containing descriptions of individual aspects of everyday life. The work examines a letter of a private nature, which reveals several aspects from the past: the private life and relationships of people in the family, the ethics of mental behavior in society, the tactics and techniques used by the warring parties during military campaigns, the names of historical figures, the language of that time. Based on the research and identification of sources of the epistolary genre, the author comes to the conclusion that today the letters of a private nature from the period of the Crimean Khanate are very rare. An analysis of the contents of the letter suggests that there was correspondence between Suleiman Effendi and his wife, and this letter is Suleiman Effendi’s response to a letter sent earlier by his wife. It also turns out that letter